Timor-Leste : Country Procurement Assessment Report - World Bank (Washington, DC, 2013)
This Country Procurement Assessment Report (CPAR) focuses on four specific areas: a) the legal and regulatory framework within which public procurement currently operates, and recommendations for necessary modifications; b) the current procurement policies, procedures and institutions responsible for procurement, and identification of short- and medium-term changes needed to ensure that procurement is carried out transparently, with due regard to economy and efficiency; c) the capacity of government officials to undertake procurement efficiently, and recommendations for appropriate staffing and capacity building plans; and, d) lessons learnt in a post conflict situation. This CPAR is consistent with the analytical and advisory assistance objectives of the Transitional Support Strategy. There is need to review and revise the Regulation to take intoconsideration the environment of an independent country, and to make it compatible with UNICITRAL Model Law on Procurement, and the procurement guidelines of the Bank, Asian Development Bank (ADB), and other development partners. Thus, it is recommended that consultants assist the Government in revising the Regulation, and, that steps be taken for developing the capacity of Timorese staff in procurement. Procurement policies, rules, procedures, and manuals, including appropriate controls, should be established, so that staff handling procurement adhere to the set rules. Given the low to non-existent capacity, more time and effort should be spent on training of procurement staff, as well as local contractors, suppliers and consultants. Viewing the emergency nature of projects in the post-conflict situation, development partners should assign experienced procurement staff, able to bring in international best practices, and provide guidance to government officials regarding procurement and project implementation issues. The assessment of the CPAR is that procurement risks are "high", based on the extremely weak procurement capacity. However, limited experience to date does not indicate significant corruption. In order to mitigate the risk, the training program identified should be implemented, with funds already available under existing grants provided by the Bank and ADB.